Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp N.; Kundisch, Dennis O.; Rahman, Mohammad S. (Management Science, 2015)
We investigate the impact of delegating decision making to information technology (IT) on an important human decision bias—the sunk cost effect. To address our research question, we use a unique data set containing actual market transaction data for approximately 7,000 pay-per-bid auctions. In contrast with the laboratory experiments of previous related studies, our research presents the unique advantage of investigating the effects of IT-enabled automated bidding agents on the occurrence of a decision bias in real market transactions. We identify normatively irrational decision scenarios and analyze consumer behavior in these situations. Our findings show that participants with a higher behavioral investment are more likely to violate the assumption of normative economic rationality because of the sunk cost effect. More importantly, we observe that the delegation of auction participation, i.e., actual bidding, to IT significantly reduces the occurrence of the sunk cost effect in subsequent decisions made by the same individual. We can attribute this reduction to the comparably lower behavioral investments incurred by auction participants who delegate their bidding to IT. In particular, by mitigating different contributors of behavioral investments, delegating to IT reduces the likelihood of the occurrence of the sunk cost effect by more than 50%. This paper was accepted by Sandra Slaughter, information systems.